Pengaruh Gadget Terhadap Kehidupan Sosial Mahasiswa Di Fakultas Ilmu Komunikasi Dan Multi Media Universitas Mercubuana Yogyakarta 2021 - Meitha Tri Herliyana; Annisa Rachmawati Shaliqat; Cinta Sani; Muhamad Nastain; Nafida Hetty Marhaeni (CV. ITTC INDONESIA, 2023)
This paper was written to examine how influential gadgets have on human social life, especially students. The presence of gadgets in everyday life certainly brings many impacts. The rapid development of technology, of course, is felt by the community. This research was conducted with quantitative methods in the form of distributing questionnaires to the target to be studied. Thus, with the data obtained, it will be known how much influence the gadget has on the social life of the students of the Faculty of Communication and Multimedia, Mercu Buana University, Yogyakarta.